PENEGAKAN HUKUM PIDANA TERHADAP JUDI ONLINE DI POLDA SUMATERA UTARA KAITANNYA DENGAN KEABSAHAN PEMBUKTIAN BUKTI ELEKTRONIK - Taryono Raharja; Madiasa Ablisar; Mahmud Mulyadi; Sunarmi Sunarmi (Universitas Dharmawangsa, 2023)
ABSTRACTSoccer betting and poker are electronic crimes, but in the process of snaring offenses they often stilluse the provisions of Article 303 paragraph (1) of the Criminal Code, instead of referring to theprovisions of Law No. 11 of 2008 concerning Information and Electronic Transactions. The policyposition of Law no. 11 of 2008 is a special position according to the principle of